Cytotoxic diterpenoids from Pteris ensiformis. Issue 2 (1st February 2017) - Shi, Yu-Sheng; Zhang, Yan; Hu, Wen-Zhong; Zhang, Li-Hong; Chen, Xi; Zhang, Ning; Li, Guang; Tan, Li-Yan
Abstract: Phytochemistry investigation on Pteris ensiformis led to the isolation of a new ent-kaurane diterpenoid, ent-kaurane-6 β, 16 α -diol-3-one (1 ), along with five known diterpenoids (2 –6 ) and three known sesquiterpenes (7 –9 ). Their structures were established by means of spectroscopic methods. The ethanol extract and the isolated compounds (1 –9 ) were evaluated for their antitumor activity against three cancer cell lines. Abstract :